For a new pedagogical humanism. Between existential void and aspiration to fullness - D'Alessio, Chiara (Formazione & insegnamento, 2017)
This work is an excursus about the nodal questions of pedagogical theoresis concerning the idea of humanism and of the human being, considering theories that have strongly contributed to the discussion on these themes, specifically the existential analysis of V.E. Frankl and its pedagogical applications. Moreover, there are hints from various researchers on the idea of freedom related to happiness, with particular reference to issues related to the formation of moral personality. The work ends with a proposal-provocation that deals about the problematic joints of contemporary education with a reference to its meaning and its foundation.